2005
DOI: 10.1002/path.1753
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐based detection of neonatal changes to branching morphogenesis reveals different mechanisms of and predicts prostate enlargement in mice haplo‐insufficient for bone morphogenetic protein 4

Abstract: Early changes to branching morphogenesis of the prostate are believed to lead to enlargement of the gland in adult life. However, it has not been possible to demonstrate directly that alterations to branching during the developmental period have a permanent effect on adult prostate size. In order to examine branching morphogenesis in a quantitative manner in neonatal mice, a combination of imaging and computational technology was used to detect and quantify branching using bone morphogenetic protein 4 haplo-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Recent work in a mouse model system has shown that BMP4 heterozygous adult animals have enlarged prostates due to increased branching of the prostate ducts during neonatal development [25]. BMP4 has also been shown to inhibit growth of the prostate cancer cell line LNCaP [26] and induce the expression of ID1, ID2, and ID3 in cell lines [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in a mouse model system has shown that BMP4 heterozygous adult animals have enlarged prostates due to increased branching of the prostate ducts during neonatal development [25]. BMP4 has also been shown to inhibit growth of the prostate cancer cell line LNCaP [26] and induce the expression of ID1, ID2, and ID3 in cell lines [23].…”
Section: Discussionmentioning
confidence: 99%
“…BMP4 inhibits budding in UGS organ culture and this effect can be overcome by the BMP antagonist NOGGIN (Cook et al, 2007;Lamm et al, 2001). Detailed analysis of the Bmp4 null heterozygote showed that functional haploinsufficiency for Bmp4 was associated with increased prostatic budding (Almahbobi et al, 2005) and increased indices of branching morphogenesis (Lamm et al, 2001). Our results show that, in the presence of DHT, SHH and the BMP4 antagonist NOGGIN induce supernumerary budding in the cultured UGS.…”
Section: Discussionmentioning
confidence: 99%
“…7). Hh signaling has been identified as a positive regulator of normal budding (Doles et al, 2006;Lamm et al, 2002;Podlasek et al, 1999) while BMP4 has been shown to be an inhibitor of prostatic budding (Almahbobi et al, 2005;Lamm et al, 2001). Thus, the RA-induced increase in prostatic bud formation may be mediated by reciprocal changes in expression of Shh and Bmp4.…”
Section: Ra Induced Reciprocal Changes In the Mrna Abundance Of Shh Amentioning
confidence: 99%
“…The postnatal development of the AROMϩ prostate was examined the computational analysis of branching morphogenesis, as previously described. 20 This analysis revealed that the postnatal development of the AROMϩ prostate was completely normal.…”
Section: Postnatal and Early Life Development Of The Aromϩ Prostate Imentioning
confidence: 98%
“…20 Briefly, VP or AP were dissected from the urogenital tracts of neonatal day 0 and day 3 wildtype and AROMϩ mice and prepared for wholemount immunostaining of epithelial cell cytokeratins. Six parameters of branching were recorded and analyzed; specifically, prostate ductal length, volume, number of main ducts, branches, branch points, and tips.…”
Section: Quantitation Of Branching Developmentmentioning
confidence: 99%